The history of the Jews in the Greco-Roman world - Schäfer, Peter, 1943- (Routledge, 2003)
Examines Judaism in Palestine throughout the Hellenistic period, from Alexander the Great's conquest in 334 BC to its capture by the Arabs in AD 636.
Repr. with corrections. - Originally published as: The history of the Jews in antiquity. [Great Britain] : Harwood Academic, 1995.
Keywords: Jews -- Palestine -- History.; Judaism -- Palestine -- History -- Post-exilic period, 586 B.C.-210 A.D.; Judaism -- Palestine -- History -- Talmudic period, 10-425.; Palestine -- History -- To 70 A.D.; Palestine -- History -- 70-638.; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D.; Judaism -- History -- Talmudic period, 10-425.; Juifs -- Palestine -- Histoire.; Judaïsme -- Histoire -- 586 av. J.-C.-210 (Période postexilique); Judaïsme -- Histoire -- 10-425 (Période talmudique); Palestine -- Histoire -- Jusqu'à 70.; Palestine -- Histoire -- 70-638.; Judaïsme -- Palestine -- Histoire -- 586 av. J.-C.-210 (Période postexilique); Judaïsme -- Palestine -- Histoire -- 10-425 (Période talmudique); HISTORY -- Ancient -- General.; Jews; Judaism -- Post-exilic period (Judaism); Judaism -- Talmudic period; Middle East -- Palestine; Joden.; Klassieke oudheid.; Jews -- History -- 586 B.C.-70 A.D., Exilic and Second Temple period.; To 638; History